Measuring School Support for Learning English as a Foreign Language through SSELL - Samiullah Sarwar; Shelina Bhamani (Journal of Education and Educational Development, 2020)
Schools label themselves to be English medium considering that by implementing textbooks in English language and adopting English as a medium of instruction is sufficient to be English. In this regard, there is a need for a checklist or selfassessment tool to enable the schools to evaluate themselves to see their positioning as an English medium school as well as understanding their role in it. This study aimed to develop a scale to enable the English language teaching practitioners to explore if the non-elite schools successfully fulfilled this claim. The scale construction methodology was used to carry out this investigation. The sample comprised of 134 participants including school principals, coordinators and teachers randomly selected using convenient sampling methods. A reliability analysis was carried out to establish the authenticity and applicability of the tool. A satisfactory score of test-retest reliability revealed the scale as a good fit to evaluate school support for English language learning; therefore, the scale can be stated as acceptable based on its psychometric properties.
Keywords: English language; official language policy; scale construction; school assessment